2005
DOI: 10.1542/peds.2004-2588
|View full text |Cite
|
Sign up to set email alerts
|

Combined Influence of Body Mass Index and Waist Circumference on Coronary Artery Disease Risk Factors Among Children and Adolescents

Abstract: These findings provide some evidence that a combination of BMI and WC should be used in clinical settings to evaluate the presence of elevated health risk among children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
163
1
25

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(211 citation statements)
references
References 31 publications
19
163
1
25
Order By: Relevance
“…In particular the representative 50th percentile for WC (which reflects waist size in the population) was higher in the USA national data collected from 1988 to 1994 29 than in these ethnic Chinese children in Hong Kong (Figure 3). Data relating WC to CV risk factors in different child populations are scant 15,34,38,39,47,48 and valid comparisons are limited by differences in methodology (non-random population sampling, different sites of WC measurement, selection and number of CV risk factors) and/ or failure to include more than one of the inter-related variables (WC percentiles, WC risk threshold percentiles and cutoff values) in the same study. The only methodologically comparable study to derive WC risk thresholds percentiles and gender-and age-related cutoff values is the Bogalusa study of 2597 Black and White American children, 34 in which three-or-more of the same six CV risk factors as in the present study were used.…”
Section: Discussionmentioning
confidence: 99%
“…In particular the representative 50th percentile for WC (which reflects waist size in the population) was higher in the USA national data collected from 1988 to 1994 29 than in these ethnic Chinese children in Hong Kong (Figure 3). Data relating WC to CV risk factors in different child populations are scant 15,34,38,39,47,48 and valid comparisons are limited by differences in methodology (non-random population sampling, different sites of WC measurement, selection and number of CV risk factors) and/ or failure to include more than one of the inter-related variables (WC percentiles, WC risk threshold percentiles and cutoff values) in the same study. The only methodologically comparable study to derive WC risk thresholds percentiles and gender-and age-related cutoff values is the Bogalusa study of 2597 Black and White American children, 34 in which three-or-more of the same six CV risk factors as in the present study were used.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 1 we present 15 papers, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] all of which used different sets of variables, number of criteria and cutoff points to define the risk-factors associated with the MS. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] The main differences concern the techniques used to estimate adiposity (body mass index (BMI) and/or waist circumference (WC)), and the variable(s) chosen to evaluate glucose metabolism (fasting glucose, …”
Section: Actual Featuresmentioning
confidence: 99%
“…12 Nonetheless, the three proposed definitions have been used in several studies carried out in pediatric populations, which reported high-prevalence of the MS in obese children and adolescents. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results of these studies varied according to the selected diagnostic criteria used, as established by a recent comparison study. 34 Moreover, in an evaluation of the different prevalence yields using different definition, Goodman et al 35 found that ATP III definition identified half as many children and adolescents as having MS as did WHO definition in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…Waist circumference has been shown to provide information on coronary artery risk factors in children and adolescents beyond that provided by BMI alone. 16,17 We found no effects of school activity on BMI or BMI s.d. scores, nor any significant differences in the development of obesity as indexed by the IOTF criteria.…”
Section: Discussionmentioning
confidence: 58%
“…Eleven of the schools admitted boys and girls and the others were single sex, which is characteristic of the British school system. Data collection started in 1999 with 4320 students in year 7 (age [11][12] and continued annually to year 11 (age [15][16]. Two schools withdrew after year 10 because of staff changes at the school.…”
Section: Setting and Participantsmentioning
confidence: 99%